Physical-chemical study of anthracene selective oxidation by a Fe(III)-phenylporhyrin derivative (2019)
In this work, we studied the anthracene oxidation by hydroxyl radicals. Hydroxyl radical was generated by reaction of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin Fe (III) (TPPFe) with hydrogen peroxide under visible radiation at a nitrogen atmosphere. The TPPFe was synthesized by Adler Method followed by metal complexation with Fe (III) chloride hexahydrate. Hydroxyl radical was detected by fluorescence emission spectroscopy and we studied kinetic of anthracene selective oxidation by hydroxyl radicals through the diﬀerential method. The TPPFe was characterized by UV-Vis spectrophotometry, Dynamic Light Scattering (DLS) and Scanning Electron Microscopy (SEM) measurements. The results indicated that TPPFE was compound by micro-particles with a size distribution of around 2500 nm. Kinetic results showed that the apparent rate constant for the oxidation of anthracene increased exponentially on as temperature increases, furthermore, the activation energy for the Anthracene oxidation by hydroxyl radicals under visible irradiation was 51.3 kJ/mol. Finally, anthraquinone was the main byproduct generated after oxidation of anthracene by TPP-Fe under visible irradiation.